PENGARUH ANALISIS JABATAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA BINJAI - Nastriana, Putri; Budiarta, Kustoro (Politeknik Bisnis Indonesia, 2025)
This study aims to analyze the effect of job analysis and career development on employee performance at the Binjai City Transportation Office. The primary goal of this study is to determine whether career development and job analysis have a simultaneous or partial impact on employee performance. Between May and September of 2024, 105 employees of the Binjai City Transportation Office participated in the study, which was likewise sampled using the complete sampling technique. A Thurstone scale questionnaire was used to gather data, and SPSS software was used for quantitative analysis. The findings demonstrated that job analysis significantly and favorably affects employee performance; in other words, the more structured and transparent the job analysis, the better the performance that results. Career development programs can boost employee motivation and competence, as evidenced by the positive and considerable impact they have been shown to have on employee performance. At the same time, career development and job analysis have a favorable and noteworthy impact on worker performance. These results highlight the value of career development initiatives and organized position planning in enhancing public organizations' performance.